(untitled) - Interest, Human; Human Interest (Washington, D.C., 2000)
The book is a beguiling story of two women from two different generations who come under the spell of India. The book is evocative of British colonial India, as well as of India of the nineteen seventies. During both eras, Anglo-Indian relations are pivotal to the budding romances. The book is evocative of the rhythms of Indian life in all its richness and tumultuousness, as well as its lingering poverty and superstitions. It is redolent of a time gone by and hopeful of what is to come. It is also an interesting dichotomy of the good and bad in both cultures, Anglo and Indian, and the influence that both cultures have on these two women, who are so different, yet so alike
Keywords: Heat and dust